Declining mortality in older people with type 2 diabetes masks rising excess risks at younger ages: a population-based study of all-cause and cause-specific mortality over 13 years. (18th January 2021) - Sacre, Julian W; Harding, Jessica L; Shaw, Jonathan E; Magliano, Dianna J
Abstract: Background: Excess mortality in people with vs without type 2 diabetes (T2DM) has fallen, but it is unclear whether men/women at all ages have benefited and which causes of death have driven these trends. Methods: All-cause and cause-specific mortality rates and excess mortality [by mortality rate ratios (MRRs) relative to the non-diabetic general population] were examined in 1 268 018 Australians with T2DM registered on the National Diabetes Services Scheme (2002–2014). Results: Age-standardized mortality decreased in men (−2.2%/year; P trend < 0.001) and women with T2DM (−1.3%/year; P trend < 0.001) throughout 2002–14, which translated to declines in the MRRs (from 1.51 to 1.45 in men; 1.59 to 1.46 in women; P trend < 0.05 for both). Declining mortality rates in T2DM were observed in men aged 40+ years and women aged 60+ years ( P trends <0.001), but not at younger ages. However, the only age group in which excess mortality declined relative to those without diabetes was 80+ years ( P trends < 0.05); driven by reductions in excess cancer-related deaths in men and cardiovascular disease (CVD) in women. Among age groups <80 years, CVD and cancer MRRs remained similar or increased over time, despite falls in both CVD and cancer mortality rates. MRRs for non-CVD/non-cancer-related deaths increased in 60–79 year-olds, but were otherwise unchanged. Conclusions: Declining excess mortality attributable to T2DM from 2002–14 was driven entirely by reductions in those aged 80+ years. Declines in total mortality among those with T2DM were apparent in more age groups, but often to a lesser extent than in the general population, thereby serving to increase the excess risk associated with T2DM.